IMPLEMENTASI KEBIJAKAN PEMBENTUKAN KAMPUNG ADAT DI KABUPATEN JAYAPURA: POTENSI, PELUANG DAN TANTANGAN - Yanuarius Turot; Mudiyati Rahmatunnisa; Jossy Ardiwisastra (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
This article discusses the potential, challenges and opportunities of the region in relation to the policy of forming customary villages. To examine this problem, Charles O Jones's (1996) policy implementation theory and James Coleman's (2008) theory of social capital are used. According to Jones (1996), the success of policy implementation can be seen in a broad dimension and concretely distinguished by the dimensions of organization, interpretation and application. Meanwhile, social capital in society is considered as an adhesive element so that policies can be implemented. This study is a literature study using regulations, government documents, scientific references and news as the main data source. The data analysis was done qualitatively with an effort to describe and explore the object under study as a whole. This study concludes that the policy to form customary villages has potential and opportunities within the framework of special autonomy accompanied by social capital support rooted in indigenous Papuan indigenous and tribal communities. However, the challenges of realizing special autonomy also vary, particularly in relation to the organizational dimensions and interpretation of policy implementation. The exploitation of existing potentials and opportunities as well as efforts to overcome challenges in policy implementation are crucial issues in the effort to form customary villages that are effective and sustainable.